ChemInform Abstract: Palladium‐Catalyzed Annulation of Diarylamines with Olefins Through C—H Activation: Direct Access to N‐Arylindoles. Issue 15 (April 2015) - Sharma, Upendra; Kancherla, Rajesh; Naveen, Togati; Agasti, Soumitra; Maiti, Debabrata
Abstract: The title process is widely applicable to olefins including styrenes, aliphatic and cycloaliphatic olefins.